Supporting Volunteer Firefighter Well-Being: Lessons from the Australian "Black Summer" Bushfires. Issue 2 (2nd April 2022) - Smith, Erin; Holmes, Lisa; Larkin, Brigid; Mills, Brennen; Dobson, Mark
Abstract: Introduction: The 2019-2020 "Black Summer" bushfires in Australia focused the attention of the nation on the critical role that volunteer firefighters play in the response to such a disaster, spurring a national conversation about how to best support those on the frontline. The objective of this research was to explore the impact of the Black Summer bushfires on volunteer firefighter well-being and to investigate how to deliver effective well-being support. Methods: An explorative qualitative design underpinned by a phenomenological approach was applied. Participant recruitment followed a multi-modal sampling strategy and data were collected through semi-structured, in-depth interviews. Results: Qualitative data were collected from 58 participants aged from 23 to 61-years-of-age (average age of 46 years). All self-reported as volunteer firefighters who had responded to the Black Summer bushfires in Australia. Just over 80% of participants were male and the majority lived in the Australian states of New South Wales (65%) and Victoria (32%). All participants reported impact on their well-being, resulting from cumulative trauma exposure, responding to fires in local communities, intense work demands, minimal intervals between deployments, and disruption to primary employment. In regard to supporting well-being, four key themes emerged from data analysis: (1) Well-being support needs to be both proactive and reactive and empower local leaders to "reach in" while encouraging responders to "reach out;" (2) Employee Assistance Programs (EAPs) should not be the only well-being support option available; (3) The sharing of lived experience is important; and (4) Support programs need to address self-stigmatization. Conclusion: Participants in this research identified that effective well-being support needs to be both proactive and reactive and holistic in approach.